A Preliminary Study Of Fruit Handling By Captive Bornean Orangutans Pongo Pygmaeus Pygmaeus And The Effects On Seed Germination - Jayasilan, Mohd. Azlan; Tracy, Pail; Sundai, Silang (IUCN, 2015)
A preliminary study to investigate the efficacy of Northwest Bornean Orangutans (Pongo pygmaeus pygmaeus) as seed dispersers and predators was conducted in Matang Wildlife Centre, Kuching, Sarawak from November 2012 to April 2013. This wildlife facility is one of the official holding centres for orangutans in Malaysian Borneo. Three adult and three juvenile captive orangutans were fed with nine species of locally-available fruits. Approximately 1.5 kg of fruit was given once daily during the study period. Seeds from sieved faecal matter were collected and tested for germination. Three species of small-seeded plants germinated while two mediumseeded plants did not. The seeds from the other four species were damaged and not tested for germination. Fruit and seed-handling behaviour was also observed. A broad range of fruit-processing behaviour such as swallowing, spitting and masticating allows the orangutans to be both seed disperser and predator towards some large-seeded and small-seeded fruits. The morphological characteristics of seeds and age of orangutans appear to influence the fate of seed dispersal.